2013
DOI: 10.1097/ijg.0b013e318259aa47
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of a New Position-independent Rebound Tonometer

Abstract: Measurements obtained with the RTPRO, either in the upright or in the supine position, show good correlation and agreement with those provided by applanation and dynamic contour tonometry. The study was registered with the DRKS (German Clinical Trials Register; http://www.germanctr.de; DRKS00000581).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 21 publications
3
30
1
1
Order By: Relevance
“…Jablonski et al 11 has reported similar values for comparable tonometers: the mean difference they observed between measurements from Icare PRO and a representative GAT in the sitting position was 0.1 mm Hg (95% LOA: À 3.6 to 3.8 mm Hg), and that between measurements from Icare PRO and Perkins HAT in the supine position was À0.4 mm Hg (95% LOA: À5.1 to 4.3 mm Hg). Furthermore, the fact that the mean difference between measurements from Icare PRO and Kowa HAT was not affected by CCT in our results (r s = 0.11, P = 0.201 while sitting; r s = À 0.06, P = 0.507 while supine) agreed well with the results of Jablonski et al, 11 who also found no relationships between CCT and the mean difference between measurements from Icare PRO and their representative GAT.…”
Section: Icare Pro Versus Goldmann-type Applanation Tonometerssupporting
confidence: 94%
See 1 more Smart Citation
“…Jablonski et al 11 has reported similar values for comparable tonometers: the mean difference they observed between measurements from Icare PRO and a representative GAT in the sitting position was 0.1 mm Hg (95% LOA: À 3.6 to 3.8 mm Hg), and that between measurements from Icare PRO and Perkins HAT in the supine position was À0.4 mm Hg (95% LOA: À5.1 to 4.3 mm Hg). Furthermore, the fact that the mean difference between measurements from Icare PRO and Kowa HAT was not affected by CCT in our results (r s = 0.11, P = 0.201 while sitting; r s = À 0.06, P = 0.507 while supine) agreed well with the results of Jablonski et al, 11 who also found no relationships between CCT and the mean difference between measurements from Icare PRO and their representative GAT.…”
Section: Icare Pro Versus Goldmann-type Applanation Tonometerssupporting
confidence: 94%
“…11 However, neither the extent of interdevice agreement between Icare PRO and the portable tonometer Tonopen XL nor the intradevice repeatability of Icare PRO measurements in the sitting versus supine positions has been reported. To pursue these aims, in this study, we evaluated the interdevice agreement for IOP measurements taken by 3 portable tonometers-the new Icare PRO rebound tonometer, the Tonopen XL Mackay-Marg tonometer, and a representative Goldmann-type HAT (Kowa HAT)-as well as the intradevice repeatability of each tonometer between readings from the sitting and supine positions.…”
mentioning
confidence: 98%
“…Their study, in keeping with prior publications, also demonstrates an increase in IOP when going from the upright to the supine position. 13 Our study found a small (<1 mm Hg) but statistically significant increase in IOP with the change in a child's position from sitting to supine. This IOP increase was measureable and was of comparable magnitude with both the Icare PRO and the Tono-Pen instruments.…”
Section: Discussionmentioning
confidence: 82%
“…13,15,16 These studies have all been performed in adults and have demonstrated that the Icare PRO, similar to the Icare, correlates well with both GAT and Tono-Pen and that it reads generally higher than GAT. Jablonski et al 13 recently reported that the Icare PRO correlates well with GAT and Perkins tonometry, as they compared the tonometers and also measured the effect of body position on IOP.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation